Ibnu Thufayl's Concept Education: The Study of Hayy Ibn Yaqzan - Intan Nur Faizah; Hafidz Hafidz; Chusiatun Chusiatun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This article examines the philosophy of education proposed by Ibn Ṭufayl as reflected in Hayy ibn Yaqẓān, aiming to reconstruct its epistemological framework, pedagogical methodology, and educational objectives, as well as to assess its relevance to contemporary education. Methodology: This study employs a qualitative approach through library research, utilizing conceptual, hermeneutic, and reflective analysis of the primary text alongside recent scholarly literature in the fields of philosophy of education and Islamic education. Results: The findings indicate that Ibn Ṭufayl’s educational epistemology is gradual and integrative, beginning with sensory experience, developing through rational reasoning, and culminating in intuitive-spiritual insight. Methodologically, education is understood as a natural process that positions the environment as the primary learning space and learners as active subjects of discovery, while the role of the teacher shifts toward that of a reflective facilitator. Educational aims in Ibn Ṭufayl’s perspective extend beyond cognitive mastery toward existential transformation that integrates knowledge, values, and character formation. Applications/Originality/Value: This study further demonstrates that Ibn Ṭufayl’s thought has strong relevance to the challenges of twenty first century education, particularly in experiential learning, self directed learning, reflective practice, and the integration of ethical and spiritual dimensions. Nevertheless, its application requires contextual adaptation to suit the pluralistic and institutional realities of modern education. This article contributes to the discourse of Islamic educational philosophy by offering a holistic, humanistic, and contextual educational model.